Alan Turing: Artificial intelligence as human self‐knowledge. Issue 6 (December 2015) - Guo, Ting
Abstract : This article explores the life and ideas of Alan Turing (1912–1954), commonly known as the father of artificial intelligence (AI), and highlights the process whereby the human self is reconceptualized in the development of Turing's ideas of machine intelligence. I will further illustrate how this process of self‐reconceptualization – composed of the pursuit, adaptation and transformation of self‐knowledge – is closely related to contemporary digital life. In doing so, I wish to reveal the ways in which Turing's underlying self‐transforming agenda of AI can contribute to our understanding of the human self, for AI, as I will argue, leads to questions of existence and existential anxieties.